Apolipoprotein E knock-out and knock-in mice: atherosclerosis, metabolic syndrome, and beyond - Pendse, Avani A. (American Society for Biochemistry and Molecular Biology, 2009)
Given the multiple differences between mice and men, it was once thought that mice could not be used to model atherosclerosis, principally a human disease. Apolipoprotein E-deficient (apoEKO) mice have convincingly changed this view, and the ability to model human-like plaques in these mice has provided scientists a platform to study multiple facets of atherogenesis and to explore potential therapeutic interventions. In addition to its well-established role in lipoprotein metabolism, recent observations of reduced adiposity and improved glucose homeostasis in apoEKO mice suggest that apoE may also play a key role in energy metabolism in peripheral organs, including adipose tissue. Finally, along with apoEKO mice, knockin mice expressing human apoE isoforms in place of endogenous mouse apoE have provided insights into how quantitative and qualitative genetic alterations interact with the environment in the pathogenesis of complex human diseases.